FREQUENCY OF HYPERTENSION IN STROKE PATIENTS PRESENTING AT AYUB TEACHING HOSPITAL - Khan, Jehangir; Rehman, Attique -ur-; Shah, Ashfaq Ali; Jielani, Asif (Journal of Ayub Medical College Abbottabad, 2006)
Background; Stroke is a frequent medical problem occurring in patients with hypertension and other risk factors. The objective of this study was to find the frequency of hypertension as important risk factor in stroke patients presenting at Medical 'B' unit of Ayub Teaching Hospital, Abbottabad from November 2003 to January 2005. Methods: Patients who clinically presented with features of stroke and then confirmed on C.T scan were included in this study. Other underlying risk factors were diabetes mellitus, smoking, cardiovascular disease and dyslipidemia. Result: Hypertension was found to be the most common risk factor in current study. Out of 91 cases, 51 (56.04%) were suffering from hypertension. Thirty five patients were male and sixteen patients were female. Peak stroke prone age was 61-70 years in males and 51-60 years in females. Conclusion: Hypertension is the leading risk factor of stroke. It is therefore essential to detect and treat hypertension at its outset Keywords: Stroke, Hypertension, Risk factors, CT scan